The Impact of Lean Supply Chain Practices on Cost Performance among SMEs in Ghana - Agbedam, Stephen Kwablah (International Journal of Supply Chain and Logistics, 2026)
Purpose: Lean supply chain practices have become a strategic approach to enhance cost performance through process optimization, waste reduction, and continuous improvement. However, empirical research on the relationship between lean supply chain practices and cost performance in Ghana's Small and Medium-sized Enterprises (SMEs) is limited. This study investigates the association between lean supply chain practices and cost performance among Ghanaian SMEs. Methodology: A quantitative research design was employed, with data collected through self-administered questionnaires from 133 staff, employees, and consumers from SMEs in the Greater Accra region. Findings: The findings reveal a statistically significant positive relationship between lean supply chain practices and cost performance. Correlation analysis showed a substantial relationship between the two dimensions, and regression analysis confirmed that lean practices had a meaningful impact on cost outcomes. Unique Contribution to Theory, Policy and Practice: The findings emphasize the need for SMEs to move beyond discrete, lean technologies and adopt more integrated, collaborative supply chain methods to fully capitalize on the strategic potential of lean as a system-wide approach to performance improvement